O fenômeno da referenciação nas tiras de Armandinho: uma análise sobre a construção das anáforas em textos multimodais - Costa, Aline Gabrielle Correia da (2022)
The present master thesis intends to develop a study about the phenomena of linguistic referencing in comic strips of the character Armandinho, by the Brazilian comic artist Alexandre Beck. Thus, we undertake a theoretical study that is based on three main approaches: Textual Linguistics, Functional Linguistics, and Semiotics. Textual Linguistics, in this work, contributes by supporting transphrastic analyses, to identify and characterize the co-referential and non-coreferential processes of texts. Functional Linguistics, through an approach that aims to explain the regularities observed in the interactive use of language, will conduct the analyzes helping to observe the conditions in which the occurrence of referential phenomena occurs. In this way, we use Semiotics from the Grammar of Visual Design, a theoretical-methodological tool that presents a perspective for the analysis of images and other multisemiotic resources. In this sense, referencing is a discursive activity that consists of the construction and reconstruction of objects of speech characterized by the resumption of elements. Considering that the strips are multimodal texts that have a dynamic character and that favor and reflect discursive and social purposes from different themes, we seek to investigate the referential sequence processes, emphasizing the constitutive and inherent verbal-visual orchestration to the strips. The objective of the dissertation, therefore, is to investigate the occurrence of these phenomena to identify how they constitute themselves as articulators of textual cohesion and their contribution to the construction of meanings in the strips. For the theoretical framework, we rely on authors such as Cunha (2008; 2015), Marcuschi (2001; 2002; 2006; 2008), Neves (2006; 2018), Koch (2005; 2015), Cope and Kalantzis (2006; 2013), Kress and Van Leeuwen (2006), Mondada (2005), Jewitt; Bezemer e O’halloran (2016), Ramos (2007; 2009; 2013; 2017) among others. From the study and analysis undertaken, it was possible to observe that the referential phenomena present in the strips, which occur primarily through anaphoras, occur through the junction of verbal text and image, which signals the increasing importance of the multimodality within linguistic studies. In addition, it was evident that the referencing processes take place beyond the linguistic, because, for the effective recovery and insertion of new referents in the text, it is necessary to activate processes and actions of a cognitive and socio-historical-cultural nature of the reader, being these factors indispensable for the global understanding of the strips and the humorous and critical purposes proposed by the author.